In Pursuit of Phrenic Nerve-Sparing Regional Anesthesia For Awake Shoulder Manipulation In Patients With Adhesive Capsulitis - Syahrul Mubarak Danar Sumantri (Indonesian Journal of Anesthesiology and Reanimation, 2021)
Introduction. While interscalene brachial plexus block remains the gold standard of any shoulder procedure, including shoulder manipulation in patients with adhesive capsulitis, anesthesiologists are reluctant to face the risk of phrenic nerve paresis, especially in patients with preexisting pulmonary conditions. Hence, many studies have targeted specific regional anesthesia of the shoulder low enough by the blockade level, leaving phrenic nerve function intact but still providing satisfying anesthesia for shoulder procedures. Until recently, no comparison between these regional anesthesia techniques focusing on shoulder manipulation for adhesive capsulitis has been published. Case Report. We compared the profiles between suprascapular nerve block, shoulder interfascial plane block, and superior trunk block as the sole anesthesia technique in patients with adhesive capsulitis undergoing awake shoulder manipulation. Conclusion. This report descriptively signifies superior trunk block excellence among other regional anesthesia techniques in achieving complete anesthesia for awake shoulder manipulation in patients with adhesive capsulitis while sparing the phrenic-nerve function